PENGARUH LABA BERSIH, INVESTMENT OPPORTUNITY SET, GROWTH POTENTIAL DENGAN LEVERAGE SEBAGAI VARIABEL KONTROL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Lusiana, Lusiana; Indriyenni, Indriyenni; Claudy, Chintya (IAIN Batusangkar, 2019)
This study aims to determine the influence of Net Income, Investment Opportunity Set, GrowthPotential with Leverage as partial and simultaneous control variables on dividend policy. This researchis classified as causal research. The population in this study were all manufacturing companies listed onthe Indonesia Stock Exchange in 2013-2017. The sample of the research was ten companies determinedby purposive sampling method. The research used secondary data obtained from www.idx.co.id. It wasanalyzed by applying panel data regression analysis. The research results obtained based on the partialtest (t test) were: (a) There is a significant effect of Net Income on dividend policy. (b) There is a significantinfluence of Investment Opportunity Set on dividend policy. (c) There is no significant influence of GrowthPotential on dividend policy. Based on the results of the research above, it is expected that the companycan increase the Investment Opportunity Set by increasing the stock market price. In term of Net Profit,it can be increased with the company's revenue and performance, while in increasing Growth Potential,it can be obtained by adding assets every year